2010
DOI: 10.1177/0961203310381511
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse alveolar hemorrhage in systemic lupus erythematosus: risk factors and clinical outcome: results from affiliated hospitals of Catholic University of Korea

Abstract: This study was undertaken to investigate clinical characteristics of diffuse alveolar hemorrhage (DAH) in patients with systemic lupus erythematosus (SLE) and to determine risk factors and clinical outcomes of DAH in SLE patients. Among the 1521 patients with SLE admitted between January 1993 and June 2009 to affiliated hospitals of Catholic University of Korea, 21 SLE were admitted for DAH. The inclusion criteria for DAH was defined as new infiltrates on chest radiographs, an acute hemoglobin drop of at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 19 publications
(34 reference statements)
3
54
0
3
Order By: Relevance
“…Diffuse alveolar hemorrhage (DAH) is a rare pulmonary complication of systemic lupus erythematosus (SLE) with a frequency ranging from 0.52% to 5.7% [1][2][3][4]. Once the patients are diagnosed with DAH, it is usually life-threatening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffuse alveolar hemorrhage (DAH) is a rare pulmonary complication of systemic lupus erythematosus (SLE) with a frequency ranging from 0.52% to 5.7% [1][2][3][4]. Once the patients are diagnosed with DAH, it is usually life-threatening.…”
Section: Introductionmentioning
confidence: 99%
“…Once the patients are diagnosed with DAH, it is usually life-threatening. The mortality rate is over 50% [1,4,5]. Though the pathogenesis of DAH is not very clear yet, Hughson MD et al [6] suggested that it might be related to the immune complex deposition in alveolar wall and the induction of apoptosis in alveolar macrophages and other smaller cells.…”
Section: Introductionmentioning
confidence: 99%
“…The most common pulmonary manifestation is pleuritis, but the most devastating pulmonary complication is pulmonary hemorrhage with a mortality rate reported to be as high as 70-90% [4,5]. In most cases DAH develops in patients with established SLE, often in the setting of active other organ involvement, including nephritis or neuropsychiatric lupus [1,4,5]. In the current case, the patient presented with DAH as the first clinical manifestation of SLE without lupus nephritis or other organ involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse alveolar hemorrhage (DAH) occurs in only 5.4% of systemic lupus erythematosus (SLE) patients, although its mortality rate reaches 61.9% [1]. In response, aggressive immunosuppressive therapies such as cyclophosphamide are commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…DAH is an uncommon pulmonary manifestation in SLE but bears an ominous prognosis [106] . DAH occurs mainly in the setting of a pulmonaryrenal syndrome and requires high-dose corticosteroids plus immunosuppressants to obtain remission [107] .…”
Section: Pulmonary Thromboembolismmentioning
confidence: 99%